New paradigm for Internet of things:intelligent spectrum-Internet of things - Qihui WU; Ran WANG; Zhenyan HUANG (物联网学报, 2018)
The electromagnetic spectrum has become an indispensable national strategic resource in the information age.With the rapid development of the world’s integrated information network,aviation vehicles,and electromagnetic spectrum airspace operations,electromagnetic space faces three major challenges:the increasing shortage of spectrum resources,increasingly stringent spectrum security,and increasingly fierce spectrum confrontation.In order to deal with the three major challenges,the basic concepts and architecture of intelligent spectrum-Internet of things (IS-IoT) was proposed,and the key technologies and future application directions of the system was analyzed.The development of IS-IoT will provide a new paradigm for the Internet of things and a new solution to the conflict between the supply and demand of spectrum resources.